Correlations of external social capital in social organizations providing integrated eldercare services with medical care in China - Ling Tang; Zhongliang Bai; Kai Ji; Ying Zhu; Ren Chen (BMC, 2022)
Abstract Background This study aimed to explore the external social capital of social organizations (SOs) providing integrated eldercare services with medical care in Anhui Province, China. Specifically, we studied the current situation and influencing factors of external social capital and its six dimensions. Methods We conducted a cross-sectional study in Anhui Province, China using a multi-stage stratified random sampling method. We employed Pearson correlation analysis and a binary logistic regression model. Results The final analysis included 49 SOs. Most organizations had a high score in norm dimension (81.6%), participation (61.2%), trust (65.3%), common language (65.3%), and social capital (63.3%). After adjusting for all covariate variables, integrated eldercare services with medical care SOs which served more than 65 elderly people were likely to report lower score in social capital. Conclusions By examining the current situation of integrated eldercare services with medical care SOs in China, this study enriched the relevant evidence of integrated medical and nursing SOs and provides a certain reference value for relevant management departments when formulating policies.